Observations on the diet of the Starry skate, Raja asterias Delaroche, 1809 (Elasmobranchii: Rajidae) in the Adriatic Sea - SVIBEN, SONJA; TRKOV, DOMEN; MAVRIČ, BORUT; KRUŽIĆ, PETAR; LIPEJ, LOVRENC (Mediterranean Marine Science, 2019)
Diet of immature specimens of the Starry skate (Raja asterias) was investigated in three different parts of the northern Adriatic Sea. Decapod crabs were found to be the skate’s primary food source, followed by teleost fish and cephalopods. An ontogenetic shift in the diet towards teleost fish was observed. No significant differences were noted comparing the diet of 22 females and 63 males, 81 juveniles and 4 adults and different size groups. The prey species preferences were different for the specimens feeding on the Italian side of the northern Adriatic, but nonetheless decapods remained the preferred food source.